Effectiveness of Compassion-based Therapy on Self-Criticism and Sexual Schemas in Women with Breast Cancer - Anooshiravani, Elham; Razeghi, Narges; Nouhi, Shahnaz; Aghae, Hakime (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to evaluate the effectiveness of compassion-based therapy on self-criticism and sexual schemas in women with breast cancer. Methods: The method of this research was quasi-experimental using pre-test, post-test and follow-up design with two experimental and control groups. The statistical population of this study included all female patients with breast cancer in Imam Khomeini Hospital (RA) who referred to this hospital in 2009-2010. According to the announced statistics, there were about 250 people and among them using Available sampling 30 people were randomly selected and randomly assigned to experimental and control groups (each group consisting of 15 people). Then, Thomson and Zoroff (2004) self-criticism questionnaires and Anderson and Siranowski (1994) sexual schemas were completed by both groups. After that, the compassion-based treatment program (Gilbert, 2009) was implemented on the experimental group. Then, the questionnaires mentioned above were completed again by both groups. Data were analyzed using SPSS software version 24 and repetitive measurement variance analysis method. Results: The findings showed that the interaction effect of stages and groups was significant for comparative variables (F=10.12), internal (F=11.85), passionate (F=28.05), explicit (F=14.42) and shy (F=6.93). (P